2009
DOI: 10.1080/02571862.2009.10639942
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microencapsulated alachlor on South African sunflower (Helianthus annuusL.) cultivars

Abstract: The microencapsulated formulation of alachlor is becoming increasingly popular for use on sunflower in South Africa, where it is registered for use at a rate of 1.54 to 1.92 kg ai ha -1. Some injury symptoms, apparently herbicide induced, have been observed on sunflower where this herbicide has been applied in the field. The response of 22 commercially available sunflower cultivars was tested in a glasshouse experiment using both a sand (10% clay, 0.24% C) and a sandy loam soil (20% clay, 0.52% C). Five rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…This differential tolerance among cultivars has been reported for various herbicides and in a number of different crops. Various researchers have reported cultivar response differences in a number of crops to herbicides within the acetamide group of herbicides (Voges & Nel, 1974;Narsaiah & Harvey, 1977;Bernards et al, 2006;Allemann & Ceronio, 2007;2009) . Bernards et al (2006) reported that the greatest factor in acetamide injury to crops may be sensitivity of inbred lines or cultivars to the herbicide.…”
Section: Introductionmentioning
confidence: 99%
“…This differential tolerance among cultivars has been reported for various herbicides and in a number of different crops. Various researchers have reported cultivar response differences in a number of crops to herbicides within the acetamide group of herbicides (Voges & Nel, 1974;Narsaiah & Harvey, 1977;Bernards et al, 2006;Allemann & Ceronio, 2007;2009) . Bernards et al (2006) reported that the greatest factor in acetamide injury to crops may be sensitivity of inbred lines or cultivars to the herbicide.…”
Section: Introductionmentioning
confidence: 99%